QUALITY ASSESSMENT OF ACADEMIC LIBRARY PERFORMANCE: THE CASE OF AN IRANIAN ACADEMIC LIBRARY - Babalhavaeji, Fahimeh; Moghaddam, Alireza Isfandyari; Aqili, Seyed Vahid; Shakooii, Ali (Malaysian Journal of Library and Information Science, 2009)
The present research aims to assess the performance of libraries at the Islamic Azad University, Sciences and Research Branch (IAUSRB) through gap analysis. To do this, a researcher-developed questionnaire which is based on available standards and quality assessment tools including ACRL standards, LibQUAL and ISO 11620, and some criteria included in the related literature was designed and distributed among users of IAUSRB libraries. Five service quality categories, were included in the questionnaire: "Environment, equipment and physical facilities", "Public services", "Non-book materials", "Staff (librarians and their co-workers)", and "Information literacy and use education". Based on research findings, the most expected library services prioritized by users are "operation time" (mean = 4.2300), "staff" (mean = 4.1461), and "circulation" (mean = 4.1208), while the least expected library services which are of lower importance from users’ perspective are "press" (mean = 3.9734) and "audiovisual materials" (mean = 3.8796). The findings also indicate that services offered by the libraries surveyed had a relatively quality performance and average success (perceived quality is 2.9635â‰ˆ50%). In other words, such a finding emphasizes an average performance of IAUSRB libraries. In addition, confirming five research hypotheses concerning gap analysis, there was a significant difference between expected quality of five service categories and their perceived quality based on users’ viewpoint. It was also realized that the categories with better performance or perceived quality from users’ perspective are "staff" (mean = 3.2240), "information literacy and user education" (mean = 2.9998), and "environment, equipment and physical facilities" (mean = 2.9871), and the two libraries "Theology and Philosophy" (mean = 2.2639) and "Medical Engineering" (mean = 2.4507) have offered poor services than the other IAUSRB libraries.